Breastfeeding and childhood wheeze: age-specific analyses and longitudinal wheezing phenotypes as complimentary approaches to the analysis of cohort data - Quigley, M; Carson, C; Kelly, Y (Oxford University Press, 2018)
Systematic reviews suggest that breastfeeding is associated with a lower risk of asthma, although marked heterogeneity exists. Using UK Millennium Cohort Study data (n = 10,126 children born 2000-2001), we examined the association between breastfeeding duration and wheezing in the past year, first at each age-group separately (age 9 months, 3, 5, 7 and 11 years) and then as a longitudinal wheezing phenotype: ‘early transient’ (wheezing any time up to age 5 but not thereafter); ‘late onset’ (any time from age 7 but not beforehand); ‘persistent’ (any time up to age 5 and any time from age 7). The association between breastfeeding and wheeze varied by age (interaction two-sided P = 0.0003). For example, breastfeeding for 6-9 months was associated with lower odds of wheezing at age 9 months, 3, and 5 years, but less so at age 7 and 11 years (adjusted odds ratios 0.73, 0.78, 0.79, 0.84, 1.06 respectively). There was a strong dose response relationship for breastfeeding per month and early transient wheeze (adjusted linear trend OR 0.961, 95% CI: 0.942, 0.980), but no clear trend for late onset or persistent wheeze. Our results identified heterogeneity in the association between breastfeeding and wheezing according to age at wheezing and wheezing phenotype.